Handbook of International Research in Mathematics Education. - English, Lyn D. (Taylor and Francis, 2002)
This state-of-the-art Handbook brings together important mathematics education research that makes a difference in both theory and practice--research that:anticipates problems and needed knowledge before they become impediments to progress;interprets future-oriented problems into researchable issues;presents the implications of research and theory development in forms that are useful to practitioners and policymakers; andfacilitates the development of research communities to focus on neglected priorities or strategic opportunities. The volume represents a genuine attempt by contributors from a.